2016
DOI: 10.1016/j.jrras.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low dose ionizing radiation effect on some blood components in animal model

Abstract: risk during exposure to irradiation. Much effort must be done and focused on establishment of protocols for medical management of radiation injuries based on hematopoietic changes for biodosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…Limited data are available about effects of varying in dose-rates and accumulated dose (Fritz, 2002). Sanzari et all suggests that a significant decline in blood cell counts after ionizing radiation depends on dose (Sanzari, Cengel, Wan, Rusek, & Kennedy, 2014) which is similar to findings in some studies that examined animals model after whole-body irradiation (El-Shanshoury, El-Shanshoury, & Abaza, 2016;Sanzari et al, 2013) or have been observed in human (Fliedner et al, 2012;Rozgaj et al, 1999). But disagreement of our results could be explained by the amount of radiation doses of participants which was too low to cause a statistically significant difference in examined parameters between two years.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Limited data are available about effects of varying in dose-rates and accumulated dose (Fritz, 2002). Sanzari et all suggests that a significant decline in blood cell counts after ionizing radiation depends on dose (Sanzari, Cengel, Wan, Rusek, & Kennedy, 2014) which is similar to findings in some studies that examined animals model after whole-body irradiation (El-Shanshoury, El-Shanshoury, & Abaza, 2016;Sanzari et al, 2013) or have been observed in human (Fliedner et al, 2012;Rozgaj et al, 1999). But disagreement of our results could be explained by the amount of radiation doses of participants which was too low to cause a statistically significant difference in examined parameters between two years.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, some investigators have reported that, there is temporary hematopoietic recovery in healthy individuals after ionizing radiation exposures (Lushbaugh, Eisele, Burr Jr, Hubner, & Wachholz, 1990;Müller & Streffer, 1991). As shown by El-Shanshoury et al (El-Shanshoury et al, 2016) and some others studying on animal models, the blood cells recover within several days and weeks after low dose radiation exposure. Moreover as shown by Seed et al, hematopoietic repair was increased in canines under variable levels of chronic radiation (Seed, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have been done to find and analyze the evaluation of high and low dose ionizing radiation on hematological parameters. For instance, [2] analyze the blood variations resulting from both irradiation and time for animal rats. They found a significant reduction in WBC, platelet and RBC counts one day after irradiation increases with increasing the dose started from 0.3 to 1Gy [3] found the low dose rate on rat and dog effect the hemopoietic failure according to both total absorbed dose and on the dose-rate of multi exposures.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in total white blood cell count; lymphocytes, monocytes, neutrophils, eosinophil was observed; however, basophils were not seen. This probably could be because basophils naturally are rarely encountered granulocytes in the peripheral blood, therefore, it is not unusual for basophils to be absent [29]. Previous studies have reported similar findings [6,17,30].…”
Section: Discussionmentioning
confidence: 59%